The challenges of changing national malaria drug policy to artemisinin-based combinations in Kenya - Amin, A; Zurovac, D; Kangwana, B; Greeenfield, J; Otieno, D; Akhwale, W; Snow, R (BioMed Central, 2007)
Backgound: Sulphadoxine/sulphalene-pyrimethamine (SP) was adopted in Kenya as first line therapeutic for uncomplicated malaria in 1998. By the second half of 2003, there was convincing evidence that SP was failing and had to be replaced. Despite several descriptive investigations of policy change and implementation when countries moved from chloroquine to SP, the different constraints of moving to artemisinin-based combination therapy (ACT) in Africa are less well documented. Methods: A narrative description of the process of anti-malarial drug policy change, financing and implementation in Kenya is assembled from discussions with stakeholders, reports, newspaper articles, minutes of meetings and email correspondence between actors in the policy change process. The narrative has been structured to capture the timing of events, the difficulties and hurdles faced and the resolutions reached to the final implementation of a new treatment policy. Results: Following a recognition that SP was failing there was a rapid technical appraisal of available data and replacement options resulting in a decision to adopt artemether-lumefantrine (AL) as the recommended first-line therapy in Kenya, announced in April 2004. Funding requirements were approved by the Global Fund to Fight AIDS, Tuberculosis and Malaria (GFATM) and over 60 million US$ were agreed in principle in July 2004 to procure AL and implement the policy change. AL arrived in Kenya in May 2006, distribution to health facilities began in July 2006 coincidental with cascade in-service training in the revised national guidelines. Both training and drug distribution were almost complete by the end of 2006. The article examines why it took over 32 months from announcing a drug policy change to completing early implementation. Reasons included: lack of clarity on sustainable financing of an expensive therapeutic for a common disease, a delay in release of funding, a lack of comparative efficacy data between AL and amodiaquine-based alternatives, a poor dialogue with pharmaceutical companies with a national interest in antimalarial drug supply versus the single sourcing of AL and complex drug ordering, tendering and procurement procedures. Conclusion: Decisions to abandon failing monotherapy in favour of ACT for the treatment of malaria can be achieved relatively quickly. Future policy changes in Africa should be carefully prepared for a myriad of financial, political and legislative issues that might limit the rapid translation of drug policy change into action.